A scoping review of force plates in female soccer: The utility, existing practice and identification of knowledge Gaps - Jack T. Fahey; Francisco Javier Robles-Palazón; Paul Comfort; Nichoals Ripley (PLoS ONE, 2026)
Female soccer has grown exponentially with increasing funding, participation and competition. Force plates enable high resolution force-time assessment using isometric and dynamic tasks for acute or longitudinal monitoring, and profiling performance and injury risk. However, more research has been conducted in male soccer players compared to females with the utility of force plates in female soccer yet to be reviewed. The purpose of this scoping review is to review existing research using force plates in female soccer describing the utility of force plates, methods used, reported metrics and to identify gaps in our current understanding. A literature search was conducted using PubMed, Google Scholar, Medline, and Cinahl using the following search terms: “girl*” OR “female*” OR “women*” AND “football*” OR “soccer*” AND “force plat*” AND “ jump” OR “isometric” AND (“multi joint*” OR “single joint*” OR “plantar flex*” OR “knee*” OR “hamstring*” OR “knee flex*” OR “hip exten*” OR “posterior chain*” OR “drop*” OR “rebound*” OR “stiffness*” “power*” OR “strength*” OR “counter*movement*” OR “dominant*” OR “non dominant*”). Sixty-three studies were eligible with most studies investigating senior elite players during dynamic tasks. The bilateral countermovement jump was the most common test followed by pre-planned change of direction and the isometric mid-thigh pull. Force plates were mostly used for performance assessment/ sex comparison research designs, followed by acute monitoring. Peak force was the most reported metric across all studies and jump height was most reported in studies investigating jumping. Most researchers used force plates in laboratory settings relating to change of direction and landing tasks with limited research conducted in applied settings and at youth level. Therefore, future researchers should focus on field-based assessments aiming to provide benchmarks and prospectively track players for injury as to support the health and performance of female soccer players at all levels of competition.